Unveiling the role of melatonin‐related gene CSNK1D in osteoclastogenesis and its implications for osteoporosis treatment - Jiewen Zhang; Shaobo Wu; Fangze Xing; Ning Kong; Yiwei Zhao; Xudong Duan; Yiyang Li; Kunzheng Wang; Run Tian; Pei Yang (Experimental Physiology)
Abstract Osteoporosis (OP) is a prevalent bone disease characterized by reduced bone density and quality, increasing fragility and fracture risk. Osteoclast (OC) activity and circadian rhythm play a role in the pathogenesis of OP. Melatonin is a circadian regulator that affects bone metabolism, but its molecular mechanism has not been studied in detail. This study aimed to identify the relationship between melatonin‐related genes and OP through bioinformatics methods and to verify it experimentally.We analysed microarray data from the GSE35959 dataset, identifying differentially expressed genes in OP patients. Circadian rhythm‐related genes and melatonin‐related genes intersect with these differentially expressed genes, highlighting that CSNK1D is a central gene. Functional enrichment, correlation and protein–protein interaction analyses were conducted. Experimental validation involved in vitro differentiation assays using RAW264.7 cells and in vivo studies with an ovariectomy‐induced rat model of OP to evaluate the role of CSNK1D in osteoclastogenesis to verify its effect on OP. Differential expression analysis revealed 272 significant genes, with CSNK1D identified as central to the circadian rhythm and to melatonin and OP interplay. Functional analyses showed involvement of CSNK1D in OC differentiation and inflammatory pathways. in vitro experiments confirmed CSNK1D upregulation during OC differentiation, and small interfering RNA‐mediated knockdown reduced OC marker expression and TRAP+ cell formation. in vivo, CSNK1D expression is associated with bone loss in OP rats. Melatonin‐related CSNK1D promotes OC differentiation and promotes the development of OP. These findings suggest CSNK1D as a potential therapeutic target for OP, offering insights into new treatment strategies integrating circadian rhythm regulation.